2007
DOI: 10.1002/dneu.20339
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation promotes peripheral axon regeneration by enhanced neuronal neurotrophin signaling

Abstract: Electrical stimulation of cut peripheral nerves at the time of their surgical repair results in an enhancement of axon regeneration. Regeneration of axons through nerve allografts was used to evaluate whether this effect is due to an augmentation of cell autonomous neurotrophin signaling in the axons or signaling from neurotrophins produced in the surrounding environment. In the thy-1-YFP-H mouse, a single 1 h application of electrical stimulation at the time of surgical repair of the cut common fibular nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(86 citation statements)
references
References 41 publications
1
85
0
Order By: Relevance
“…Electrical stimulation has been demonstrated in rat femoral nerves to increase intrinsic BDNF and NT-4 expression in injured motoneurons and promote neuroregeneration after injury (2,15). In this study, a statistically significant upregulation of BDNF mRNA in the stimulated Onuf's nucleus was noted both 2 days and 1 wk after injury and stimulation compared with the shamstimulated side.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Electrical stimulation has been demonstrated in rat femoral nerves to increase intrinsic BDNF and NT-4 expression in injured motoneurons and promote neuroregeneration after injury (2,15). In this study, a statistically significant upregulation of BDNF mRNA in the stimulated Onuf's nucleus was noted both 2 days and 1 wk after injury and stimulation compared with the shamstimulated side.…”
Section: Discussionmentioning
confidence: 48%
“…Electrical stimulation has been demonstrated to promote neuroregeneration after injury and to increase intrinsic BDNF expression in injured neurons (1,2,15,19). Stimulation could therefore provide a method for facilitation of recovery by promoting neuroregeneration and reinnervation if the muscle is damaged simultaneously, such as in childbirth injury.…”
mentioning
confidence: 99%
“…7c) [7]. Using transgenic mice that express yellow fluorescent protein in a small proportion of their axons and by cross-breeding of these mice with mice in which neurotrophic factor expression was deleted, English et al [66] demonstrated the critical role of the neurotrophic factors brainderived neurotrophic factor (BDNF) and neurotrophin 4/5 in the efficacy of the electrical stimulation effect in accelerating nerve regeneration [66]. Exogenous administration of either BDNF or GDNF did not increase nerve regeneration after immediate nerve repair (Fig.…”
Section: The Role Of Neurotrophic Factors and Androgens In The Efficamentioning
confidence: 99%
“…Several strategies that enhance axon regeneration after peripheral nerve transection have been identified, e.g. proteoglycan degradation (Groves et al, 2005), electrical stimulation (Al-Majed et al, 2000;English et al, 2007) and exercise (Sabatier et al, 2008), but far less is understood about whether function is restored when axon regeneration is enhanced (Varejao et al, 2004). A better understanding of the slope-related specificity of muscle activation and hindlimb control in intact and injured animals may help in efforts to identify strategies that ultimately enhance function.…”
Section: Introductionmentioning
confidence: 99%